2007
DOI: 10.1177/0961203307081914
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of young patients with pediatric-onset, long-standing lupus nephritis with tacrolimus given as a single daily dose: an open-label pilot study

Abstract: The objective of the current work is to report the preliminary experience with tacrolimus (TL) administered as a single-dose daily for maintenance therapy of young patients with pediatric-onset, long-standing systemic lupus erythematosus (SLE). Six consecutive patients with long-standing SLE were recruited for a 6-month open-label trial of single-dose-daily administration of tacrolimus (3 mg/day) without dose up of concomitantly administered prednisolone (PDN). TL treatment was started at the time of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…The therapeutic range of blood concentration relating to the e‹cacy of tacrolimus in lupus nephritis is still unknown. 19) As the limitations of this study were the small number of patients, veriˆcation of these observations will require further studies with an increased patient sample size. Because AUC is generally thought to be correlated with trough concentration (C 12 h ) in transplant patients who are treated with tacrolimus twice a day, blood tacrolimus concentrations are monitored by C 12 h .…”
Section: Discussionmentioning
confidence: 87%
“…The therapeutic range of blood concentration relating to the e‹cacy of tacrolimus in lupus nephritis is still unknown. 19) As the limitations of this study were the small number of patients, veriˆcation of these observations will require further studies with an increased patient sample size. Because AUC is generally thought to be correlated with trough concentration (C 12 h ) in transplant patients who are treated with tacrolimus twice a day, blood tacrolimus concentrations are monitored by C 12 h .…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Tac combined with PDN has been successfully administered without serious adverse effects, as induction and maintenance treatment for patients with proliferative and membranous lupus nephritis (Politt et al, 2004;Maruyama et al, 2005;Mok et al, 2005;Tse et al, 2007;Szeto et al, 2008). However, there is little information regarding the efficacy and safety of Tac in young patients with lupus nephritis (Tanaka et al, 2007a(Tanaka et al, , 2009). The safety of Tac treatment is important because of its potent nephrotoxicity.…”
Section: Tacrolimus a Calcineurin Inhibitormentioning
confidence: 99%
“…Although these patients did not necessarily have permanently high blood levels of Tac (Duddridge & Powell, 1997;Tse et al, 2007), the development of an optimal Tac treatment strategy for lupus nephritis, with a dose as low as possible, is sought to minimize treatment toxicity while maintaining treatment efficacy. In this context, in Japan, Tac is usually administered once daily for patients with rheumatoid arthritis (RA) or lupus nephritis since once-daily administration of Tac is the governmental approved protocol (Kawai & Yamamoto, 2006;Tanaka et al, 2007aTanaka et al, , 2009Asamiya et al, 2009). Kawai and Yamamoto (2006) reported the safety of Tac administered at a dose of 1.5-3.0 mg once daily for the treatment of RA even in the elderly.…”
Section: Tacrolimus a Calcineurin Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclosporine A (CsA) and tacrolimus (Tac) are T cell-specific calcineurin inhibitors that prevent activation of helper T cells, thereby inhibiting the transcription of interleukin (IL)-2 and proinflammatory cytokines such as tumor necrosis factor-α, IL-1β, and IL-6 [7,8]. Recently, CsA and Tac combined with prednisolone (PDN) have been observed to be useful to treat difficult cases of LN, including pediatric-onset cases [7,9,10,11,12,13,14,15,16,17,18,19,20]. These studies found that both CsA and Tac ameliorated the clinical activity of lupus and exerted an anti-proteinuric effect in LN.…”
Section: Introductionmentioning
confidence: 99%